A Comparison of Multiple Data Sources to Identify Vaccinations for Veterans with Spinal Cord Injuries and Disorders - Weaver, Frances M. (American Medical Informatics Association, 2004)
Monitoring vaccination activity requires regular access to information about patient vaccination status. This report describes our experience using multiple Department of Veterans Affairs (VA) data sources to determine availability and completeness of vaccination information for veterans with spinal cord injuries and disorders (SCI&D). Administrative and clinical databases were limited to coding vaccine administration, undercounted vaccinations, and were unable to account for whether the vaccine was offered and the reasons for nonreceipt. Medical record review provided more detail but was labor intensive and costly. Patient surveys provided the richest information but were costly, time-consuming, and based on a sample of patients. Agreement was poor between data sources. This report suggests that while VA is well positioned to use national databases for clinical care decisions and to inform policy, vaccination data were incomplete. Electronic records must include data that are consistently entered and validated before they can be useful for care management and decision making.